THE EFFICIENCY OF THE GREEK TRAVEL AGENCIES AS A DETERMINING FACTOR FOR THE GREEK TOURISM MARKET - Galanakis, Spiros (2007)
The main object of the present dissertation is to study the competitiveness of Greek tourism. Therefore, we provide evidence regarding the tourist demand for Greece and we examine the strong and the weak points of the Greek tourism market, the opportunities and the threats it is faced with. Moreover, we examine the market of the Greek travel agencies and we aim at identifying the factors, which lead to their inefficiency. In order to do this, we use a questionnaire that was distributed to the managers of the main Greek travel agencies. Based on the answers given and using the statistical program SPSS 12.0, we get to some important conclusions regarding the travel agencies and their future.